IMPLEMENTASI KOMPETENSI KEPRIBADIAN GURU AKIDAH AKHLAK DALAM PEMBINAAN AKHLAK SISWA KELAS V DI MIN 3 SAMBAS - Walini Walini (Tarbiya Islamica, 2015)
The purpose of this study is to find out: 1) personality competencies that must be possessed by Akidah Akhlak teachers in moral development for fifth grade students at MIN 3 Sambas in the 2020-2021 academic year. 2) Implementation of teacher personality competencies carried out by Akidah Akhlak teachers in the moral development of fifth grade students at MIN 3 Sambas for the 2020-2021 academic year. 3) Supporting and inhibiting factors in the implementation of teacher personality competencies carried out by Akidah Akhlak teachers in the moral development of fifth grade students at MIN 3 Sambas for the 2020-2021 academic year. This study uses a descriptive method with a qualitative approach. The data collection techniques used interviews, observations, and documentation, while the data analysis techniques were carried out, namely: data reduction, data display, verification and conclusion drawing, while the technique of checking the validity of the research data used 2 techniques, namely: triangulation and member check.The results showed that: The personality competencies that Akidah Akhlak teachers must possess in the moral development of fifth grade students at MIN 3 Sambas in the 2020/2021 academic year consist of: having faith and piety to Allah SWT, being responsible, having a strong spirit and having stable emotions, being able to behave mature, honest, disciplined, fair, wise and authoritative, being a role model for students and the community, able to evaluate their own performance, and able to develop abilities. The implementation of the Akidah Akhlak teacher's personality competence in the moral development of fifth grade students at MIN 3 Sambas for the 2020/2021 academic year is carried out by applying the traits and values ​​embedded in the teacher's personality. Supporting factors in implementing the personality competence of Akidah Akhlak teachers in the moral development of fifth grade students at MIN 3 Sambas are madrasa rules and regulations, madrasa cooperation with parents and the community, facilities and infrastructure, extracurricular activities, and the community environment. The inhibiting factors consist of different students' personalities, a less supportive family environment, technology, limited time and supervision, and the Human Rights Law which limits teachers.